Remimazolam Anesthesia for MitraClip Implantation in a Patient with Advanced Heart Failure. (5th May 2021) - Satoh, Tomoe; Nishihara, Noriaki; Sawashita, Yasuaki; Ohno, Sho; Hirata, Naoyuki; Yamakage, Michiaki
Abstract : Remimazolam, a novel and ultrashort-acting benzodiazepine, has been available for general anesthesia in Japan. The administration of remimazolam does not induce injection pain, has been reported to have less cardiovascular depressant effects during general anesthesia, and flumazenil can antagonize the effects of remimazolam. However, in clinical trials, no patient who is complicated with severe heart failure or undergoes cardiac surgery was included. We present anesthetic management with remimazolam for MitraClip ® implantation in a patient with severe mitral regurgitation and advanced heart failure. Remimazolam was administered both in anesthetic induction and maintenance with less cardiovascular depressant effects. After surgical procedures were completed, the patient smoothly recovered from anesthesia and the tracheal was extubated just after administration of flumazenil. Remimazolam may be able to achieve appropriate anesthetic management in patients complicated with severe cardiovascular diseases.